The nexus between economic growth, financial development, trade openness, and CO₂ emissions in European countries - Lamia Jamel; Samir Maktouf (Cogent Economics & Finance, 2017)
In this paper, we empirically investigate the causal nexus between economic growth (GDP), CO2 emissions (environmental degradation), financial development, and trade openness using the ordinary least squares technique for a yearly panel data of 40 European economies, during the period of study from 1985 to 2014. To examine this causal link, we utilize the Cobb-Douglas production function. The empirical findings point to a bidirectional Granger causal linkage among GDP and pollution, GDP and financial sector development, GDP and trade openness, financial sector development and trade openness, and trade openness and pollution in the case of European economies. From the causal link between GDP and environmental pollutants, we validate the existence/confirm the validity of the environmental Kuznets curve hypothesis. Also, we confirm/bear out the feedback suggestion of the bidirectional causality among trade openness and financial sector development. Besides, we find the neutrality hypothesis linking carbon emissions and financial sector development inflows. We find the presence of the bidirectional nexus between GDP and financial sector development and among GDP and trade openness in the European economies. Finally, panel causality verifies that bidirectional causal connection is found between economic growth, environmental degradation (CO2), financial development, and trade openness.
Keywords: C3; F1; G2; O4; Q4; Q5; 330; economic growth; CO2 emissions; financial development; trade openness; European economies